3D bio-printed biphasic scaffolds with dual modification of silk fibroin for the integrated repair of osteochondral defects. (28th May 2021) - Deng, Changxu; Yang, Jin; He, Hongtao; Ma, Zhenjiang; Wang, Wenhao; Zhang, Yuxin; Li, Tao; He, Chuanglong; Wang, Jinwu
Abstract : Repair of osteochondral defects is still a challenge, especially the regeneration of hyaline cartilage. Abstract : Repair of osteochondral defects is still a challenge, especially the regeneration of hyaline cartilage. Parathyroid hormone (PTH) can inhibit the hypertrophy of chondrocytes to maintain the phenotype of hyaline cartilage. Here, we aimed to construct a bio-printed biphasic scaffold with a mechanical gradient based on dual modification of silk fibroin (SF) for the integrated repair of osteochondral defects. Briefly, SF was grafted with PTH (SF-PTH) and covalently immobilized with methacrylic anhydride (SF-MA), respectively. Next, gelatin methacryloyl (GM) mixed with SF-PTH or SF-MA was used as a bio-ink for articular cartilage and subchondral bone regeneration. Finally, the GM + SF-PTH/GM + SF-MA osteochondral biphasic scaffold was constructed using 3D bioprinting technology, and implanted in a rabbit osteochondral defect model. In this study, the SF-PTH bio-ink was synthesized for the first time. In vitro results indicated that the GM + SF-MA bio-ink had good mechanical properties, while the GM + SF-PTH bio-ink inhibited the hypertrophy of chondrocytes and was beneficial for the production of hyaline cartilage extracellular matrix. Importantly, an integrated GM + SF-PTH/GM + SF-MA biphasic scaffold with a mechanical gradient was successfully constructed. The results in vivo demonstrated that the GM + SF-PTH/GM + SF-MA scaffold could promote the regeneration of osteochondral defects and maintain the phenotype of hyaline cartilage to a large extent. Collectively, our results indicate that the integrated GM + SF-PTH/GM + SF-MA biphasic scaffold constructed by 3D bioprinting is expected to become a new strategy for the treatment of osteochondral defects.